Benign thyroid nodules with RAS mutation grow faster. (28th September 2015) - Puzziello, Alessandro; Guerra, Anna; Murino, Alessia; Izzo, Giulia; Carrano, Mario; Angrisani, Elisabetta; Zeppa, Pio; Marotta, Vincenzo; Faggiano, Antongiulio; Vitale, Mario
Summary: Context: The management of a benign thyroid nodule includes follow‐up until its size requires a surgical or alternative treatment. To date, it is difficult or impossible to predict the size changes of a benign nodule in a given patient because no specific growth parameters exist. RAS mutations have been described in thyroid adenomas and hyperplastic benign nodules. Objective: The aim of this study was to establish whether the volume changes of benign nodules are associated with the presence of RAS mutation. Patients and methods: Genomic DNA obtained by fine‐needle aspiration of 78 thyroid nodules with benign cytology was analysed by pyrosequencing for the presence of NRAS 61 and KRAS 13 mutations. Ultrasonographic features were obtained. The volume of nodules at baseline and their changes after a mean follow‐up of 25 months were evaluated according to the presence of RAS mutation. Results: A RAS mutation was found in 24 thyroid aspirates (30·8%, 8 NRAS 61 and 16 KRAS 13 ). RAS mutation was not associated with ultrasonographic features, but was significantly associated with a larger size at baseline ( P = 0·017). After a 25‐month mean follow‐up, RAS mutation‐positive nodules displayed faster growth ( RAS mutation‐positive vs RAS mutation‐negative % annual growth 27·6% ±32·2% vs 1·0% ±17·0%, P < 0·001). Conclusions: Benign thyroid nodules bearing RAS mutation grow more rapidly than those with wild‐type RAS . Searching for RAS mutations in thyroid nodules with benign cytology might be useful to the clinician in choosing a more appropriate and timely surgical management.